(3GdfLe GdhgGL aj TQM GdefgGLs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s; (3Gdfhhj,J (B676 (3g` s ((3YHO GdcQje Hf aNQ GdOjf GdScfOQi GdTGaYi Gdeci s)
(3ChdgG (B:s
(3LgQi hgeSi hSejJg GdfLe GdhgGL ai TQM GdefgGL s
(3BNQgG (B:s
(3BNQg ai fgGjI HGH GdENUGQ hGdahGJ ef cJGH GdML (B" (3NGJeI jSJLH Cf jMed GdeSGaQ Edi Cgdg gOjI hJSJMH GdfbjYI hgj WYGe jYed dbOhe GdeSGaQ hGdgd CYde HGdUhGH BNQ GdLRA GdChd ef GdfLe GdhgGL s
(3HgG fXGe GdJYbjHIs
(3YdjgG JUMjMGJs
(3YdjgG JedcGJ CbOegG SfI (B1087 (3gJ HGSe Ydi Hf egOi Hf eMeO GdYei GdSeGhis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdTGaYjs